2020
DOI: 10.18063/ijb.v6i1.250
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion-Based Bioprinting through Glucose-Mediated Enzymatic Hydrogelation

Abstract: We report an extrusion-based bioprinting approach, in which stabilization of extruded bioink is achieved through horseradish peroxidase (HRP)-catalyzed cross-linking consuming hydrogen peroxide (H2O2) supplied from HRP and glucose. The bioinks containing living cells, HRP, glucose, alginate possessing phenolic hydroxyl (Ph) groups, and cellulose nanofiber were extruded to fabricate 3D hydrogel constructs. Lattice- and human nose-shaped 3D constructs were successfully printed and showed good stability in cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Horseradish peroxidase (HRP)-catalyzed gelation of aqueous solutions containing a gelatin derivative with phenolic hydroxyl (Ph) moieties (Gelatin-Ph) is one of the well-known methods, which has been used for obtaining gelatin-based hydrogels stable at around 37 °C. , Due to good cytocompatibility and biocompatibility, the hydrogels have been studied for varieties of biomedical applications, such as vehicles for retinal progenitor cell transplantation, carriers of drugs for bone regeneration, cell-laden wound dressing, and inks for bioprinting. , …”
Section: Introductionmentioning
confidence: 99%
“…Horseradish peroxidase (HRP)-catalyzed gelation of aqueous solutions containing a gelatin derivative with phenolic hydroxyl (Ph) moieties (Gelatin-Ph) is one of the well-known methods, which has been used for obtaining gelatin-based hydrogels stable at around 37 °C. , Due to good cytocompatibility and biocompatibility, the hydrogels have been studied for varieties of biomedical applications, such as vehicles for retinal progenitor cell transplantation, carriers of drugs for bone regeneration, cell-laden wound dressing, and inks for bioprinting. , …”
Section: Introductionmentioning
confidence: 99%
“…The high diversity of chemical structures and properties of these plant polysaccharides opens the possibility for their application in several fields, including in the food area (e.g., as gelling agents) [ 97 ], in the biomedical field (e.g., in drug delivery systems) [ 98 ], and, more recently, in tissue engineering [ 99 ]. The interest in using some of these plant-derived polysaccharides in the formulation of bioinks for 3D bioprinting applications has also grown considerably in the later years, as summed up in Table 2 , with several works using cellulose and nanocelluloses [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ] and pectin [ 119 , 120 ].…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…CELLINK Bioink from Cellink [ 132 ]; throughout the years, not much evolution and creativity has been observed regarding the use of NFC as a bioink component. Most recent studies still describe its combination with alginate for bioprinting of different cell lines, namely human cartilage [ 115 , 116 ], human dermis [ 117 ], bone [ 102 , 118 ], and skeletal muscle [ 103 ]. Additionally, nanocelluloses are still mainly used as reinforcing components for hydrogel bioinks due to their excellent mechanical properties.…”
Section: Polysaccharide-based Hydrogel Bioinksmentioning
confidence: 99%
“…It enables the development of kidney tissue sheets in a uniform pattern with increased nephron cells together with a functional proximal tubular, and thereby effectively improves the quality control, scale, and structure when compared to the manual organoid method [21]. In another study, an extrusion-based bioprinting approach utilized bio-ink consisting of living cells, glucose, alginate with a phenolic hydroxyl group, and cellulose nanofiber to develop lattice and human nose-shaped 3D constructs that remained stable for more than a week [22]. Gospodinova et al [23] reported that extrusion-based 3D printing helps in developing cervical cancer models by using hydroxyethyl cellulose-based bio-inks with different amounts of sodium alginate embedded with HeLa cells.…”
Section: Extrusion-based Printingmentioning
confidence: 99%